Immunofluorescence imaging of neutrophil extracellular traps in human and mouse tissues - Schönfeld, Lavinia; Appl, Birgit; Pagerols-Raluy, Laia; Heuer, Annika; Reinshagen, Konrad; Boettcher, Michael (JoVE. Video journal, 2023)
Neutrophil extracellular traps (NETs) are released by neutrophils as a response to bacterial infection or traumatic tissue damage but also play a role in autoimmune diseases and sterile inflammation. They are web-like structures composed of double-stranded DNA filaments, histones, and antimicrobial proteins. Once released, NETs can trap and kill extracellular pathogens in blood and tissue. Furthermore, NETs participate in homeostatic regulation by stimulating platelet adhesion and coagulation. However, the dysregulated production of NETs has also been associated with various diseases, including sepsis or autoimmune disorders, which makes them a promising target for therapeutic intervention. Apart from electron microscopy, visualizing NETs using immunofluorescence imaging is currently one of the only known methods to demonstrate NET interactions in tissue. Therefore, various staining methods to visualize NETs have been utilized. In the literature, different staining protocols are described, and we identified four key components showing high variability between protocols: (1) the types of antibodies used, (2) the usage of autofluorescence-reducing agents, (3) antigen retrieval methods, and (4) permeabilization. Therefore, in vitro immunofluorescence staining protocols were systemically adapted and improved in this work to make them applicable for different species (mouse, human) and tissues (skin, intestine, lung, liver, heart, spinal disc). After fixation and paraffin-embedding, 3 µm thick sections were mounted onto slides. These samples were stained with primary antibodies for myeloperoxidase (MPO), citrullinated histone H3 (H3cit), and neutrophil elastase (NE) according to a modified staining protocol. The slides were stained with secondary antibodies and examined using a widefield fluorescence microscope. The results were analyzed according to an evaluation sheet, and differences were recorded semi-quantitatively. Here, we present an optimized NET staining protocol suitable for different tissues. We used a novel primary antibody to stain for H3cit and reduced non-specific staining with an autofluorescence-reducing agent. Furthermore, we demonstrated that NET staining requires a constant high temperature and careful handling of samples.